Biomedical Informatics Publications: a Global Perspective - Maojo, V.; Garcia-Remesal, M.; Bielza, C.; Crespo, J.; Perez-Rey, D.; Kulikowski, C. (Methods of Information in Medicine, 2012)
Background: Biomedical Informatics (BMI) is a broad discipline, having evolved from both Medical Informatics (MI) and Bioinformatics (BI). An analysis of publications in the field-should provide an indication about the geographic distribution of BMI research contributions and possible lessons for the future, both for research and professional practice.Objectives: In part I of our analysis of biomedical informatics publications we presented results from BMI conferences. In this second part, we analyse BMI journals, which provide a broader perspective and comparison between data from conferences and journals that ought to confirm or suggest alternatives to the original distributional findings from the conferences.Methods: We manually collected data about authors and their geographical origin from various MI journals: the International Journal of Medical Informatics (IJMI), the Journal of Biomedical Informatics (JBI), Methods of In-formation in Medicine (MIM) and The Journal of the American Medical Informatics Association (JAMIA). Focusing on first authors, we also compared these findings with data from the journal Bioinformatics.Results: Our results confirm those obtained in our analysis of BMI conferences – that local and regional authors favor their corresponding MI journals just as they do their conferences. Consideration of other factors, such as the increasingly open source nature of data and software tools, is consistent with these findingsConclusions: Our analysis suggests various indicators that could lead to further, deeper analyses, and could provide additional insights for future BMI research and professional activities.
Keywords: Biomedical informatics; medical informatics; bioinformatics; conference rankings; journal impact factor